KEWENANGAN OMBUDSMAN KOTA MAKASSAR DALAM PENYELESAIAN SENGKETA PELAYANAN PUBLIK : (PERSPEKTIF SIYASAH DUSTURIYAH) - Nurul Aprilia, Andi; Samin, Sabri; Chotban, Sippah (Prodi Hukum Tata Negara (Siyasah Syariyyah) Fakultas Syariah dan Hukum UIN Alauddin Makassar, 2024)
The Ombudsman is a state institution whose existance is quite important in the constitutional system, because to supervise the implementation of public services is one of the main tasks of a state government. This study aims to determine how the authority of the Makassar City Ombudsman in public services. This study uses emprical and normative research methods, whit an empirical juridical approach, normative jurdical and syar’i, the data used are secondary and primary data taken from the field, namely the Ombudsman of Makassar City. The results show that the Makassar City Ombudsman in resolving public service disputes is still not optimal due to limited authority, so that not all reports can be handled by the Makassar City Ombudsman because on of the requirements is to be domiciled in Makassar.